PEMANFAATAN DIMETHYL ETHER (DME) SEBAGAI SUBSTITUSI BAHAN BAKAR MINYAK DAN LPG - Boedoyo, Mohamad Sidik (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
As a developing country, currently the energy demand in Indonesia increases rapidly.Although Indonesia has a huge of oil reserves the production of oil fuels as the mainÃ‚Â energy consumption has not been enough and should be imported. It is devised toÃ‚Â substitute oil fuel with other resources such as liquefied coal, natural gas, biofuelsÃ‚Â and dimethyl ether (DME). In the short future, the use of DME as an alternative fuelÃ‚Â appears to be a promising approach for reducing the uses of diesel oil and LPG. It canÃ‚Â be described in to two approaches. First, due to the high cetane number of DME, itÃ‚Â can be used for compression ignition engines which have higher thermal efficienciesÃ‚Â compared to spark ignition engines. Second, due to the physical properties of DME, itÃ‚Â can substitute oil fuels and LPG uses in industries, commercials, and households forÃ‚Â lighting and cooking. Hence, DME production is not limited to one feedstock. DME canbe derived from fossil fuel feedstocks, including natural gas and coal, as well as fromÃ‚Â renewable feedstock sources such as biomass. Since Indonesia have abundant ofÃ‚Â energy sources as DME raw material, such as natural gas, coal and biomass, utilizationÃ‚Â of DME into Indonesia energy system is necessary to be developed.Key words :Energy Potential, Dimethyl Ether, Diesel Oil and LPG Substitution